MRI Atlas of Central Nervous System Tumors - Cecconi, Lucia; Pompili, Alfredo; Caroli, Fabrizio; Squillaci, Ettore (Springer Vienna, 1992)
From the review of the Italian edition in "Neurosurgery": "...The first chapter by a physicist from the Università dell'Aquila presents the scientific basis of the complex phenomenon of nuclear magnetic resonance and MR imaging in a clear and reasonably simple fashion. The next two chapters of the remaining eleven are excellent background and informational chapters; one is on MR anatomy of the brain compared with numerous appropriate anatomic sections and includes labeled reference drawings, and the other is on the classification of tumors of the central nervous system and includes a table of the MR differential characteristics of the major intracranial neoplasms. Each of the remaining chapters deals with one of the following: neuroepithelial tumors, pineal region tumors, meningiomas, neurinomas, pituitary adenomas and craniopharyngiomas, angiomas and aneurysms producing mass effect, intracranial metastatic tumors, rare tumors and expansive nontumoral lesions, and, lastly, spinal tumors. There is a brief clinical discussion on each of these topics, and each chapter is illustrated with numerous excellent reproductions of good quality MR images of these lesions. The selection, presentation, variety, and quality of the cases and the outstanding illustrations make for a superb atlas..." #H.V. Rizzoli, Washington, DC#1 This atlas is the result of the cooperative work of radiologists and neurosurgeons of the National Cancer Institute in Rome. The English edition has been enriched with many new images. This has been necessary because of the actual wide use of Gadolinium as a contrast agent and the use of more sophisticated software for MR angiography